Microstructured platforms to study nanotube-mediated long-distance cell-to-cell connections - Abel, Marcus Patrick; Riese, Sigrid; Schlicker, Oliver; Bukoreshtliev, Nickolay V.; Gerdes, Hans-Hermann; Spatz, Joachim P.; Rustom, Amin (Biointerphases, 2011)
Recently, numerous innovative approaches have attempted to overcome the shortcomings of standard tissue culturing by providing custom-tailored substrates with superior features. In particular, tunable surface chemistry and topographical micro- and nanostructuring have been highlighted as potent effectors to control cell behavior. Apart from tissue engineering and the development of biosensors and diagnostic assays, the need for custom-tailored platform systems is accentuated by a variety of complex and poorly characterized biological processes. One of these processes is cell-to-cell communication mediated by tunneling nanotubes (TNTs), the reliable statistical analysis of which is consistently hampered by critical dependencies on various experimental factors, such as cell singularization, spacing, and alignment. Here, the authors developed a microstructured platform based on a combination of controlled surface chemistry along with topographic parameters, which permits the controllable attachment of different cell types to complementary patterns of cell attracting/nonattracting surface domains and—as a consequence—represents a standardized analysis tool to approach a wide range of biological questions. Apart from the technical complementation of mainstream applications, the developed surfaces could successfully be used to statistically determine TNT-based intercellular connection processes as they are occurring in standard as well as primary cell cultures.
Gesehen am 23.02.2022